On the evolution of switching oxide traps in the HfO2/TiN gate stack subjected to positive- and negative-bias temperature stressing - Gao, Yuan (2014)
In this paper, evolution of switching oxide traps (SOTs) in the HfO2/TiN gate stack is examined under positive- and negative-bias temperature (PBT and NBT, respectively) stress. Charging and discharging of SOTs were sensed by repetitive stress/ relaxation cycling and the discharging of SOTs was quantified based on the extent of the threshold voltage shift recovery after a fixed relaxation interval. For both the PBT and NBT stress at a low oxide field (~5.5 MV/cm), the quantity of SOTs discharged is observed to be approximately constant, independent of the number of stress/relaxation cycles. At a higher oxide stress field (~7 MV/cm), however, the quantity of SOTs discharged is seen to decrease progressively with the number of stress/relaxation cycles. This observation implies that a part of the SOTs which can be discharged in earlier relaxation phases is no longer able to do so as the stress progresses. The reduction in recovery points to an increase of the emission times of the trapped charge arising probably from structural changes at the oxide defect sites. Although the evolution of SOTs under both stresses is broadly similar, differences are observed from the opposite gate-polarity relaxation study and stress-induced leakage current measurement. First-principles simulation shows that a defect model based on the oxygen vacancy alone could not explain the differences observed. An extended model involving both the oxygen vacancy and vacancy-interstitial defects is shown to be able to explain the similarities as well as differences observed under PBT and NBT stresses.